A guide to outcome modeling in radiotherapy and oncology : listening to the data - El Naqa, Issam (Series in medical physics and biomedical engineering)
"This book discusses outcome modeling in cancer using analytical and data-driven approaches, both top-down using big data approaches and bottom-up using multi-scale methods. It provides in-depth mathematical background as well as intuitive physical and biological perspectives. Applications in radiation oncology, chemotherapy, surgery and immunotherapy are covered, as well as - in the case of multimodality treatments - span assessment, prediction, prognosis, decision support and clinical trials design. This is in addition to statistical validation of performance and evaluating applicability. Software tools accompany the book, illustrating how to solve various modeling exercises"-- Provided by publisher